Placebo Justice: Victim Recommendations and Offender Sentences in Sexual Assault Cases - Walsh, Anthony (1986)
After many years of neglect, crime victims have recently been rediscovered, and concern for them has become an important item on the agenda of the criminal justice system.1 Feminist activists have exerted particular pressure on the criminal justice system to reform its attitudes and practices relating to the concerns of sexual assault victims.2 One might reasonably expect that this upsurge of concern will result in sexual assault victims exerting greater influence on decision-making at all stages of the processing of offenders